2019
DOI: 10.1088/1742-6596/1339/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

How online media and technology innovation influence consumer’s purchase intention

Abstract: This research experiment is to know how online media and technology innovation influence consumer’s purchase intention. The sample of this research were the students of UPI “yptk” Padang who followed the @ Indonesia.Jersey Instagram. There were 100 respondents. The result of the research had the positive and significant influence of online media and technology innovation toward the consumer’s purchase intention. This research has contributed to increase sales with online marketing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…20 Mulyani et al, (2019) The authors of this study found that social media and technological innovation had a positive and significant influence on the customers' purchase intentions. Social media's unique features were prominent in its technology and offered unlimited possibilities in processing and spreading the news.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…20 Mulyani et al, (2019) The authors of this study found that social media and technological innovation had a positive and significant influence on the customers' purchase intentions. Social media's unique features were prominent in its technology and offered unlimited possibilities in processing and spreading the news.…”
mentioning
confidence: 80%
“…Similar study conducted byHamadan et.al. (2019) & Mulyani et al, (2019 observed that digital and social media were used to boost product sales by increasing traffic on marketplaces. The study conducted by authors of this research had similar findings viz.…”
mentioning
confidence: 99%
“…Research results showed that the social environment, Innovativeness significantly influences online consumption intentions (Reyvina & Tunjungsari, 2022;Rizki et al 2019) and risk negatively influences online consumption intentions (Putri et al 2023). Consumption intentions also have a significant influence on online purchasing behavior (Sitohang et al 2021).…”
Section: Managerial Implicationsmentioning
confidence: 97%